Neuropeptides Exert Neuroprotective Effects in Alzheimer's Disease - Chen, Xin-Yi; Du, Yi-Feng; Chen, Lei (Frontiers in Molecular Neuroscience, 2019)
Alzheimer’s disease (AD) is an age-related neurodegenerative disorder characterized by cognitive deficits and neuronal loss. Deposition of beta-amyloid peptide (Aβ) causes neurotoxicity through the formation of plaques in brains of Alzheimer’s disease. Numerous studies have indicated that the neuropeptides including ghrelin, neurotensin, pituitary adenylate cyclase-activating polypeptide (PACAP), neuropeptide Y, substance P and orexin are closely related to the pathophysiology of Alzheimer’s disease. The levels of neuropeptides and their receptors change in Alzheimer’s disease. These neuropeptides exert neuroprotective roles mainly through preventing Aβ accumulation, increasing neuronal glucose transport, increasing the production of neurotrophins, inhibiting endoplasmic reticulum stress and autophagy, modulating potassium channel activity and hippocampal long-term potentiation. Therefore, the neuropeptides may function as potential drug targets in the prevention and cure of Alzheimer’s disease.